Development and validation of the Information Seeking Anxiety scale - Erfanmanesh, Mohammadamin; A., Abrizah; Abdul Karim, Noor Harun (Malaysian Journal of Library and Information Science, 2017)
Erfanmanesh, M., Abrizah, A., & Karim, N. H. A. (2012). Development and validation of the Information Seeking Anxiety scale. Malaysian Journal of Library & Information Science, Vol.17, no. 1: 21-39. The purpose of the study was to develop and validate the Information Seeking Anxiety Scale. The research took place in several empirical phases. First, a list of ninety-four (94) potential key components was developed by the researchers and was sent to a panel of experts for validation. Then a pilot instrument comprising ninety-three (93) statements was generated according to the list of key components and was validated again for content by the experts. The face validity of the instrument was then evaluated by a group of fifteen (15) postgraduate students. Finally, the psychometric properties of the instrument were tested with a group of four hundred (400) postgraduate students using exploratory factor analysis and Cronbach’s alpha internal reliability coefficient. Consequently a valid and reliable 47-item Information Seeking Anxiety Scale was produced which could be employed in efforts to measure information seeking anxiety among library users.